7(n+7)=19+2n

Simple and best practice solution for 7(n+7)=19+2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(n+7)=19+2n equation:


Simplifying
7(n + 7) = 19 + 2n

Reorder the terms:
7(7 + n) = 19 + 2n
(7 * 7 + n * 7) = 19 + 2n
(49 + 7n) = 19 + 2n

Solving
49 + 7n = 19 + 2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-2n' to each side of the equation.
49 + 7n + -2n = 19 + 2n + -2n

Combine like terms: 7n + -2n = 5n
49 + 5n = 19 + 2n + -2n

Combine like terms: 2n + -2n = 0
49 + 5n = 19 + 0
49 + 5n = 19

Add '-49' to each side of the equation.
49 + -49 + 5n = 19 + -49

Combine like terms: 49 + -49 = 0
0 + 5n = 19 + -49
5n = 19 + -49

Combine like terms: 19 + -49 = -30
5n = -30

Divide each side by '5'.
n = -6

Simplifying
n = -6

See similar equations:

| .3*300=x | | 0.03=6 | | 18(x-1)=12(x+3) | | 8x+10x=7 | | .3*300= | | 6(a+4)(a-7)=0 | | 7st+6su+8sv= | | X-6=7y | | 120=6x-6x | | 16x+4x=19+x | | n=5m+4 | | x+(x*.25)=183 | | (x^2+4x+4)(x^2-6x+9)=(-1) | | -3y-8=2y+17 | | (2x+39)+(x-7)+(x)=180 | | =4(a+9) | | (3r+8)(r-8)=0 | | log(x)=log(-2x+5) | | (15!)/(15-4)!4!•(.2^4)•(1-.2)^(15-4) | | 9-3(y-2)=3-3y | | 4x+5(-3)=10 | | 5x+2=-8+3x+20 | | 4v^2+0x-9=0 | | 13+16x=-5 | | 0.23-2.1x=-0.61 | | cos(x)+3x=0 | | 16=-6y+4(y+6) | | y(x-8)=5 | | -2[x-4]+7=-3 | | 15=logx | | x(.36)+y(.14)=.2 | | 16b^2-24b+9=0 |

Equations solver categories